Influência da ordem-desordem estrutural na fotoluminescência do CaTiO3:Sm - Figueiredo, Alberthmeiry Teixeira de (Universidade Federal de São Carlos, 2007)
Some properties of the materials, such as ferroelectric and optic, are dependents to structural organization of the material. Thus, to know the order disorder degree at short, intermediate and long range is important to elucidate or predict properties in materials. The PL emission at room temperature will be used to study the structural order disorder at short, intermediate and long range in the CaTiO3:Sm, in function of annealed temperature. Using studies of the structural order disorder in the CaTiO3:Sm system will propose a model that appoint to favorable conditions, in disordered material, to show PL emission at room temperature.
Influence of the order-disorder structural on the photoluminescence of the CaTiO3
Keywords: Química inorgânica; Fotoluminescência; Titanatos; Ordem-desordem estrutural; CIENCIAS EXATAS E DA TERRA::QUIMICA